1980
DOI: 10.1002/1097-0142(19800501)45:9<2404::aid-cncr2820450928>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Secretory carcinoma of the breast

Abstract: Nineteen examples of a very rare type of carcinoma of the breast have been studied. The carcinoma is unusual in that it has exaggerated secretory features previously reported only (with one exception) in juveniles. But not all the patients in our series were juveniles; they ranged in age from 9 to 69 years (median age, 25 years). Six were 30 years of age or older. Eighteen patients were female and 1 was a 9-year-old boy. Treatment varied from local excision of the tumor to radical mastectomy. Four of the 11 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
165
1
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 7 publications
4
165
1
1
Order By: Relevance
“…Cytologically, the cells are bland, have vesicular nuclei and abundant pale-pink granular or vacuolated cytoplasm. 1,2 Following the initial publication describing mammary analog secretory carcinoma, other investigators began to look back at their own institutional cases in order to reanalyze some of their salivary gland tumors. Acinic cell carcinomas, adenocarcinomas, not otherwise specified (NOS), polymorphous lowgrade adenocarcinomas, mucoepidermoid carcinomas, and cystadenocarcinomas are examples of cases re-evaluated in a small number of recently published studies, describing additional cases of mammary analog secretory carcinoma.…”
mentioning
confidence: 99%
“…Cytologically, the cells are bland, have vesicular nuclei and abundant pale-pink granular or vacuolated cytoplasm. 1,2 Following the initial publication describing mammary analog secretory carcinoma, other investigators began to look back at their own institutional cases in order to reanalyze some of their salivary gland tumors. Acinic cell carcinomas, adenocarcinomas, not otherwise specified (NOS), polymorphous lowgrade adenocarcinomas, mucoepidermoid carcinomas, and cystadenocarcinomas are examples of cases re-evaluated in a small number of recently published studies, describing additional cases of mammary analog secretory carcinoma.…”
mentioning
confidence: 99%
“…A total of 27 cases (including 2 cases from our study, see Table 3) of male patients with secretory breast carcinoma could be identified in the literature. 2,3,6,9,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Most affected patients were children and adolescents with a median age of 27 years. The tumors are usually located subareolarly.…”
Section: Discussionmentioning
confidence: 99%
“…For patients over 20 years old, an initial simple mastectomy with axillary node dissection might be adequate. 2 However, recently the technique of sentinel lymph node biopsy has replaced conventional axillary lymph node dissection to become the standard of care for early breast cancer. Thus, conservative surgery (adequate local excision or quadrantectomy) with sentinel lymph node biopsy has been chosen by some surgeons when neoplasms are smaller than 20 mm, and simple mastectomy with sentinel lymph node biopsy has been preferred for neoplasms larger than 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…McDivitt and Stewart [1] in 1966 recognized an uncommon variety of mammary carcinoma in children, which they designated as 'juvenile carcinomas'. Subsequently in 1980, Tavassoli and Norris [2] reported 19 cases in patients ranging in age from 9 to 69 years old. Based on this they recommended replacing the term 'juvenile carcinoma' with the descriptive term 'secretory carcinoma'.…”
Section: Discussionmentioning
confidence: 99%